Literasi Keuangan dalam Pengelolaan Pencatatan Laporan Keuangan UMKM - Lestari, Putri Gantine (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2024)
Community Service is one of the Tridharma of Higher Education that must be implemented by Lecturers of Higher Education. This activity is carried out every semester. This Community Service activity was carried out in 2 (two) UMKM partners, precisely located at Jl. Lengkong Kecil No.28, Paledang, Kec. Lengkong, Bandung City, West Java, 40261, Bandung City and located at Jl. Laswi No. 51, Bandung City. The UMKM actors are engaged in the culinary sector. The Community Service activity is aimed at UMKM with the aim of providing literacy information regarding recording financial reports for UMKM in accordance with SAK EMKM. It is hoped that with this PKM, UMKM can make financial reports in accordance with SAK EMKM so that UMKM can know their own financial position. The method of implementing the activity consists of 3 (three) stages. The first stage is a meeting with the Partner (UMKM) by conducting a survey. The second stage is the stage of working on UMKM financial reports routinely. The third stage is the stage of reporting the results of UMKM financial reports. The reporting is done by looking at whether the partner is experiencing a profit or loss. After that, provide recommendations to the UMKM regarding how to manage financial reports using the Buku Warung application, Microsoft Excel and manual.